The Impact of English as a Medium Instruction (EMI) on English Language Skills Development in Business Administration Students - Reski Amalia S; Walangitan Melania Rut (Hasanuddin University, 2024)
The objectives of this study were to find out whether the use of English as a Medium of Instruction (EMI) was effective in improving the English Language of Students majoring in Business Administration and to analyse the factors that influence the effectiveness of English as a medium Instruction (EMI) in improving the English Language Skills of Students majoring in Business Administration. This study employed qualitative research which the data was collected using observation and interviews. The collected data was interpreted qualitatively. This study employs purposive sampling. Class II MB 6 and IV MB 6 were the population and IV MB 6 was the sample with 30 students. The finding showed that implementing EMI can improve some aspects of English language skills, namely speaking and listening. On the other hand, some difficulties in understanding the topic delivered occurred. The factors that influence the effectiveness of English as a medium of Instruction (EMI) in improving English Language Skills are the Frequency of using English, the Frequency of listening to English speakers, and the interaction of the students with their classmates where they need to speak English during the classroom activity.